2005
DOI: 10.1590/s0034-72992005000300018
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome da apnéia e hipopnéia obstrutiva do sono: análise cefalométrica

Abstract: Obstructi ve sleep apnea and hypopnea syndrome (OSAHS) are characterized by repeated pauses in breathing during sleep, usually associated with sleep interruption and decreased oxyhemoglobin saturation. Cephalometric analysis has become an important method in diagnosis, reporting specific craniofacial characteristics such as posterior air pharyngeal space, tongue length and hyoid position, which may predispose some people to develop SAHOS. The purpose of this revision is to present several anatomic aspects by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
19

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
0
6
0
19
Order By: Relevance
“…Com o mesmo raciocínio, pode-se considerar os distúrbios do sono nas crianças respiradoras orais. Observam-se, em associação à respiração oral e à conseqüente redução do espaço da rinofaringe, sinais como baba noturna, roncos e distúrbios respiratórios decorrentes de alergia (29) e, nos casos mais graves, a síndrome da apnéia e hipopnéia obstrutiva do sono, caracterizada por episódios repetitivos de obstrução das vias aéreas superiores durante o sono, usualmente associados à interrupção do mesmo e à queda da saturação da oxihemoglobina (36) . A qualidade do sono também pode ser prejudicada na presença de rinite alérgica.…”
Section: Conclusãounclassified
“…Com o mesmo raciocínio, pode-se considerar os distúrbios do sono nas crianças respiradoras orais. Observam-se, em associação à respiração oral e à conseqüente redução do espaço da rinofaringe, sinais como baba noturna, roncos e distúrbios respiratórios decorrentes de alergia (29) e, nos casos mais graves, a síndrome da apnéia e hipopnéia obstrutiva do sono, caracterizada por episódios repetitivos de obstrução das vias aéreas superiores durante o sono, usualmente associados à interrupção do mesmo e à queda da saturação da oxihemoglobina (36) . A qualidade do sono também pode ser prejudicada na presença de rinite alérgica.…”
Section: Conclusãounclassified
“…A study (15) aimed at evaluating, in adult population, the influence of gender, body height and race on orofacial anthropometric measurements, showed that men have larger orofacial anthropometric dimensions than women. Another study (16) found that the angle between the hard palate and soft palate in men is greater than in women.…”
Section: Introductionmentioning
confidence: 94%
“…A análise cefalométrica é outro procedimento que deve ser considerada entre os exames de rotina 51 , pois permite obter informações sobre anormalidades esqueléticas, contribuindo na escolha do tratamento 52 .…”
Section: Diagnósticos Da Sahosunclassified